2014
DOI: 10.1128/aac.02483-13
|View full text |Cite
|
Sign up to set email alerts
|

Prior Exposure to Lamivudine Increases Entecavir Resistance Risk in Chronic Hepatitis B Patients without Detectable Lamivudine Resistance

Abstract: The efficacy of entecavir (ETV) treatment in chronic hepatitis B (CHB) patients who were exposed to lamivudine (LAM) but had no detectable LAM resistance (LAM-R) is not well evaluated. In this study, we aimed to evaluate whether the probability of developing genotypic resistance to ETV in LAM-exposed patients with or without LAM-R is comparable to that in antiviral-naive patients. This retrospective cohort study included 500 consecutive patients with CHB who started ETV monotherapy at a single tertiary hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 32 publications
1
32
2
1
Order By: Relevance
“…Studies involving ETV have revealed that its use as a first‐line therapeutic agent can reduce the rate of resistance (≤1%), even after 5 years of therapy . However, the current findings show that the long‐term use of the drug in naïve patients, as well as other antiviral drug‐resistant patients increase the incidence of ETV resistance . Sequential data support the fact that for ETV resistance, the mutation at residue rtT184, rtS202, rtM250, and rt169, is required.…”
Section: The Current Development and Treatment For Chronic Hepatitissupporting
confidence: 51%
See 1 more Smart Citation
“…Studies involving ETV have revealed that its use as a first‐line therapeutic agent can reduce the rate of resistance (≤1%), even after 5 years of therapy . However, the current findings show that the long‐term use of the drug in naïve patients, as well as other antiviral drug‐resistant patients increase the incidence of ETV resistance . Sequential data support the fact that for ETV resistance, the mutation at residue rtT184, rtS202, rtM250, and rt169, is required.…”
Section: The Current Development and Treatment For Chronic Hepatitissupporting
confidence: 51%
“…103 However, the current findings show that the long-term use of the drug in naïve patients, as well as other antiviral drug-resistant patients increase the incidence of ETV resistance. 35,104,105 Sequential data support the fact that for ETV resistance, the mutation at residue rtT184, rtS202, rtM250, and rt169, is required. Furthermore, to adapt the ETV resistance by HBV polymerase over the preexisting LMV resistant, mutation rtM204V/rtL180M is necessary.…”
Section: Entecavirmentioning
confidence: 86%
“…Previous studies have focused on the outcome of LAM-resistant patients receiving ETV treatment as rescue therapy. [16][17][18][19] In Taiwan, CHB patients can be reimbursed by the Bureau of National Health Insurance (BNHI) for prescribed treatments, including interferon or nucleoside/nucleotide analogs (NA). However, the duration of reimbursement for treatment for HBeAg positive CHB patients is 24 weeks for interferon and 3 years for NA.…”
Section: H Epatitis B Virus (Hbv) Infection Is a Global Healthmentioning
confidence: 99%
“…A recent study showed that the efficacy of TDF was preferable to entecavir for achieving CVS in NA-experienced CHB patients without genotypic resistance, which suggests that previous antiviral treatment has clinical implications regarding the selection of an antiviral agent irrespective of preexisting genotypic resistance [14]. Likewise, our previous study showed that prior treatment with low-potency lamivudine affected the long-term efficacy of entecavir, even without genotypic resistance to lamivudine [4]. Drug-resistant mutations developed from previously used drugs are preserved in covalently closed circular DNA in the liver, and these mutations might attenuate the efficacy of subsequent drugs to which the virus was not previously exposed [15].…”
Section: Discussionmentioning
confidence: 99%
“…The primary goal of CHB therapy is to prevent disease progression and prolong survival through long-term suppression of hepatitis B virus (HBV) replication [1-3]. A recent cohort study reported that entecavir failed to show comparable efficacy in nucleos(t)ide analogue (NA)-experienced CHB patients and NA-naïve patients [4], which suggests the important role of previous treatment history in patients with CHB.…”
Section: Introductionmentioning
confidence: 99%